The intravenous injection of pethidine and dexmedetomidine in the prevention of cesarean postoperative shivering under spinal anesthesia: A double-blind clinical trial - Zahra Kamran; Behzad Nazemroaya (Mashhad University of Medical Sciences, 2022)
Introduction: Postoperative shivering is a common complication in pregnant women undergoing cesarean section with spinal anesthesia, and since no ideal method has been proposed to prevent this complication, the present study was performed aimed to compare the effect of intravenous injection of pethidine and dexmedetomidine in prevention of shivering after cesarean section under spinal anesthesia. Methods: This double-blind randomized clinical trial study was performed in 2019-2020 on 90 women candidates for cesarean section with spinal anesthesia in Alzahra and Shahid Beheshti hospitals of Isfahan. The subjects were randomly assigned to three groups (n=30 in each group). The first group received 0.25 mg pethidine, the second group 0.1 μg/kg dexmedetomidine and the third group received the same volume of normal saline. The drugs were injected intravenously immediately after fetal removal and umbilical cord clamp, and the incidence and severity of shivering in recovery were evaluated. Data were analyzed by SPSS statistical software (version 25) and One-way analysis of variance, analysis of variance with repeated observations, Chi-square and Wilcoxon tests. P< 0.05 was considered statistically significant. Results: There was a significant difference between the three groups in the incidence of shivering (P <0.001). In examining the frequency of shivering intensity in the three studied groups, the intensity of shivering in the pethidine group was less than that of dexmedetomidine, especially in grades 3 and 4, and the intensity of shivering in the two intervention groups was less than the control group (p=0.002). Conclusion: The use of both pethidine and dexmedetomidine reduces the incidence of shivering after cesarean section. Since the side effects of dexmedetomidine are less than pethidine and also due to the limitation of pethidine consumption in some patients, it seems that the use of this drug is preferable to pethidine.